Trade protection and inter-industry wages in India - PUJA VASUDEVA DUTTA (PRUS Working Paper no. 27, 2004)
Using a unique database of individual data and industry-level tariff rates and other industry characteristics, this paper examines the link between trade protection and inter-industry wage premia in India during a period of rapid trade liberalisation. These premia represent differentials solely due to the industry affiliation of the worker after controlling for other worker characteristics. This paper finds that the impact of protection on the inter-industry wage premia is substantially positive - workers employed in industries with high tariffs receive higher wages than apparently identical workers in low tariff industries. This positive tariff-wage effect is evident whether or not industry specific effects are included and is consistent with the Ricardo-Viner trade model.